Ring Theory 2007 : Proceedings of the Fifth China-Japan-Korea Conference, Tokyo, Japan, 10-15 September 2007 - Marubayashi, Hidetoshi, 1941- (World Scientific, 2009)
This volume consists of a collection of survey articles by invited speakers and original articles refereed by world experts that was presented at the fifth China-Japan-Korea International Symposium. The survey articles provide some ideas of the application as well as an excellent overview of the various areas in ring theory. The original articles exhibit new ideas, tools and techniques needed for successful research investigation in ring theory and show the trend of current research.